Development Of A Nucleic Acid Amplification Test For The Detection Of Mycobacterium Tuberculosis - Kaniappan, Priyatharisni (2015)
Tuberculosis is one of the common infectious diseases in Malaysia, caused by the airborne pathogen, Mycobacterium tuberculosis. Due to the infectious nature of the disease, diagnostic-based detection of Mycobacterium tuberculosis is vital for effective disease management, surveillance, epidemiological purpose and for the administration of a prompt treatment. Current diagnostic methods rely on smear microscopy and culture method; however these strategies suffer from several pitfalls. This shifts the attention towards the nucleic-acid based detection of M. tuberculosis, which requires the identification of suitable nucleic acid target as the diagnostic marker.